P084 AN EVALUATION OF THE CLINICAL COURSE AND UTILIZATION PATTERNS FOR ACUTE AND CHRONIC POUCH-RELATED CONDITIONS AMONG PATIENTS TREATED IN A MULTICENTER COHORT. (7th February 2019) - Barnes, Edward L; Raffals, Laura; Long, Millie D; Syal, Gaurav; Kayal, Maia; Ananthakrishnan, Ashwin; Cohen, Benjamin; Pekow, Joel; Deepak, Parakkal; Colombel, Jean-Frederic; Herfarth, Hans H; Sandler, Robert S
Abstract: Background: The most common complication following a proctocolectomy with ileal pouch-anal anastomosis (IPAA) is the development of pouchitis, however gaps exist in our understanding of the clinical course of pouch-related disorders. We used data from a cohort of patients from seven inflammatory bowel disease (IBD) centers in the United States to evaluate the risk factors for acute pouchitis, chronic pouchitis, and Crohn's disease (CD) of the pouch, as well as subsequent therapy and healthcare resource utilization patterns in a longitudinal analysis. Methods: For this study, we first performed a cross-sectional analysis of baseline data from the multicenter cohort to identify risk factors for the development of pouch-related conditions, therapy utilization at the time of enrollment, and baseline disease activity using the modified pouchitis disease activity index (mPDAI). We then analyzed longitudinal patterns of therapies and resource utilization patterns among patients with an IPAA. We performed bivariate analyses for all comparisons. Results: Among 481 patients with an IPAA, only 13 patients reported a preoperative diagnosis of CD. However at the time of enrollment, 193 (40%) patients had been diagnosed with CD after IPAA. Eighty-eight (18%) patients had no history of pouchitis, while 102 (21%) had acute pouchitis and 98 (20%) had chronic pouchitis. Patients with chronic pouchitis and CD demonstrated a significantly longer duration between colectomy and baseline visit and patients with CD were more likely to demonstrate a history of extraintestinal manifestations (Table 1). Among 200 patients with a history of pouchitis, 130 (65%) were using antibiotics for pouchitis at baseline (Table 2). The median follow-up time was 796 days (interquartile range 610-1043 days). In the longitudinal analysis, patients with CD of the pouch were significantly more likely to be initiated on a biologic or immunosuppressive therapy as compared to patients with acute or chronic pouchitis (34% vs 10%, p<0.001). Among patients with CD of the pouch, 32 (17%) were initiated on a new anti-tumor necrosis factor alpha (anti-TNF) therapy, 7% were initiated on ustekinumab, and 9% were initiated on vedolizumab (Table 2). Patients with CD of the pouch were also more likely to be hospitalized during the follow-up period when compared to patients with acute or chronic pouchitis (39% vs. 25%, p=0.002). Conclusions: In a multicenter cohort from seven academic IBD centers in the United States, antibiotics were the most commonly used therapies for pouchitis, however novel approaches including biologic therapies were utilized in up to 25% of patients with a pouch-related disorder. Although the rate of CD of the pouch may indicate a referral bias in this population, therapy and hospitalization patterns indicate a significant burden of disease among patients with pouch-related disorders.